Effects of α1-Acid Glycoprotein on Acute Pancreatitis and Acute Lung Injury in Rats - Muchitsch, Eva-Maria; Varadi, Katalin; Pichler, Ludwig (Arzneimittelforschung, 2000)
α1-Acid glycoprotein (AAG), a highly negatively charged glycoprotein, well known for its capillary stabilizing effect, was tested in rat models of acute edematous pancreatitis, acute hemorrhagic-necrotizing pancreatitis, and acute respiratory distress syndrome (ARDS).In cerulein-elicited edematous pancreatitis AAG improved histological alterations at 200 mg/ kg i.v. and plasma amylase activity at 1800 or 4200 mg/kg i.v. All other parameters (edema, plasma lipase) were not affected in a biologically relevant manner.In glycodeoxycholic acid-induced hemorrhagic-necrotizing pancreatitis AAG was without effect on parameters measured (plasma amylase, plasma lipase activity, histological scores) at 1800 or 4200 mg/kg i.v. At the extremely high dose of 15000 mg/kg i.v. plasma amylase and lipase levels were decreased.In lipopolysaccharide-mediated ARDS, AAG was tested at 50, 200 or 600 mg/kg i.v. AAG, but also the placebo formulation decreased the myeloperoxidase content in the bronchoalveolar lavage fluid. Histological alterations were improved by AAG, however, not by the placebo formulation. Lung water content was not significantly influenced by AAG, whereas Evans blue extravasation was significantly diminished by all three doses of AAG.It is concluded that the edematous pancreatitis is the first in vivo condition with increased extravascular fluid accumulation, in which AAG is not effective. Based on data presented here and literature data, there is evidence for a beneficial effect of AAG in acute lung injury.
Keywords: α1-Acid glycoprotein, rat; Acute respiratory distress syndrome; Edematous pancreatitis; Hemorrhagic-necrotizing pancreatitis